CSP Data: A Data Discovery Web Application of Commercial CSP Plants - Bonilla, Javier; Thonig, Richard; Carballo, Jose Antonio; Lilliestam, Johan; Alarcón-Padilla, Diego César; Zarza, Eduardo (SolarPACES 2023, 29th International Conference on Concentrating Solar Power, Thermal, and Chemical Energy Systems, 2024)
CSP Data is a free web application for data discovery of all commercial Concentrating Solar Power (CSP) plants. CSP data is fed with CSP.guru data, an open source dataset of all Concentrating Solar Power (CSP) plants. This paper introduces and explains the tools and information provided by CSP Data to potential users so they can use it efficiently together with the ongoing work being performed to release new features. It also presents the CSP.guru dataset, how the original idea was developed, its key features and how this dataset is used by industry and academi